2008
DOI: 10.1177/1049732308322604
|View full text |Cite
|
Sign up to set email alerts
|

Gauging Visibility: How Female Clerical Workers Manage Work-Related Distress

Abstract: Our aim was to explain how female clerical workers manage work-related distress, using a feminist grounded theory method. Thirty-seven interviews were conducted with 24 female clerical workers. They engage in the process of gauging visibility to manage a recognition-vulnerability paradox. To gauge visibility, they take the lay of the land by attending to threats, resources, and supports within withering or flourishing work conditions. When distressing events occur, they select tactics of taking it in, taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Our findings have shown that the women often had mixed feelings about support provided in their workplace. Some of the women spoke about supervisors who were very unsupportive or inconsistently supportive in their interactions with the women, a finding consistent with the literature (Long, Hall, Bermbach, Jordan, & Patterson, 2008).…”
Section: Discussion and Implications Composition Availability And Consistency Of Social Supportsupporting
confidence: 82%
“…Our findings have shown that the women often had mixed feelings about support provided in their workplace. Some of the women spoke about supervisors who were very unsupportive or inconsistently supportive in their interactions with the women, a finding consistent with the literature (Long, Hall, Bermbach, Jordan, & Patterson, 2008).…”
Section: Discussion and Implications Composition Availability And Consistency Of Social Supportsupporting
confidence: 82%
“…Furthermore, participants felt that transmission of knowledge changed attitudes toward SED and sick leave among supervisors and workplace colleagues. Other qualitative studies confirm that increased understanding of the reasons for sickness absence have preventive effects for RTW [14,43,54,55]. Hence, inviting "respectful communication" is important in order to improve conditions that change workplace attitudes and cultures [54].…”
Section: Discussionmentioning
confidence: 88%
“…Hence, inviting "respectful communication" is important in order to improve conditions that change workplace attitudes and cultures [54]. An additional aspect that improves workplace culture is to acknowledge how stress is talked about and create an increased awareness of the meaning of stress as a sign of engagement at the same time that it is a sign of weakness [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…They highlight potential pathways through which gender inequities can be manifested in work stress. 28 Perceived stress and associated short-term responses, for example, were often construed as a stereotypically feminine weakness (for example, oversensitivity). Further, concerns about supporting a family in the presence of job insecurity may cause distress for men, possibly via internalized societal gender role expectations (for example, men as traditional family 'bread winners').…”
Section: Discussionmentioning
confidence: 99%